Vivência de enfermeiros no cuidar de pacientes na terminalidade: um enfoque bioético - Felix, Zirleide Carlos (2014)
INTRODUCTION: With technological advances, the field of bioethics emerged as reflection to guide professionals in the health care context , in particular the practice of caring for terminally ill patients. OBJECTIVES: This study aimed to investigate the experiences of nurses in caring for patients in terminally; to analyze the experiences of nurses in caring for terminally ill patients highlighted by the principles of bioethics. METHODS: This was an exploratory study, with qualitative approach, developed in the Intensive Care Unit of the Hospital Lauro Wanderley, Federal University of Paraíba located in the city of João Pessoa (PB). The sample consisted of fifteen clinical nurses from the institution selected for the study. The research project was submitted to the Committee in Ethics Research of the hospital, which received approval certificate, with CAAE registration under paragraph 13289213.1.0000.5183. Data collection occurred from March till July 2013 by applying a formulary containing questions relevant to the proposed objectives. The empirical material was analyzed qualitatively using the technique of content analysis, following phases: pre -analysis, material exploration and using the results, inference and interpretation. RESULTS AND DISCUSSION: From the qualitative analysis emerged the following thematic categories: Category I: the experience of nurses in caring for terminally ill patients: coping and care before death; Category II: The practice of nursing care to patients in the terminally ill: bioethical principles. CONCLUSION: The study shows the commitment of nurses participating in the study regarding the care of terminally ill patients, especially with regard to bioethical principles surrounding this practice. Therefore, due the reduced amount of researches focusing on this topic in the national literature, it is expected that this study will contribute to further investigations under the care of the terminally ill patients .